The Cytoplasmic Domains of Streptococcus mutans Membrane Protein Insertases YidC1 and YidC2 Confer Unique Structural and Functional Attributes to Each Paralog - Mishra, Surabhi; Brady, L. Jeannine (Frontiers in Microbiology, 2021)
Integral and membrane-anchored proteins are pivotal to survival and virulence of the dental pathogen, Streptococcus mutans. The bacterial chaperone/insertase, YidC, contributes to membrane protein translocation. Unlike Escherichia coli, most Gram-positive bacteria contain two YidC paralogs. Herein, we evaluated structural features that functionally delineate S. mutans YidC1 and YidC2. Bacterial YidCs contain 5 transmembrane domains (TMD), 2 cytoplasmic loops, and a cytoplasmic tail. Because S. mutans YidC1 (SmYidC1) and YidC2 (SmYidC2) cytoplasmic domains (CD) are less well conserved than are TMD, we engineered ectopic expression of the 14 possible YidC1-YidC2 CD domain swap combinations. Growth and stress tolerance of each was compared to control strains ectopically expressing unmodified yidC1 or yidC2. Acid and osmotic stress sensitivity are associated with yidC2 deletion. Sensitivity to excess zinc was further identified as a yidC1 phenotype. Overall, YidC1 tolerated CD substitutions better than YidC2. Preferences toward particular CD combinations suggested potential intramolecular interactions. In silico analysis predicted salt-bridges between C1 and C2 loops of YidC1, and C1 loop and C-terminal tail of YidC2, respectively. Mutation of contributing residues recapitulated yidC1- and yidC2-associated phenotypes. Taken together, this work revealed the importance of cytoplasmic domains in distinct functional attributes of YidC1 and YidC2, and identified key residues involved in interdomain interactions.